Designing the initial processes in opening a mine and determining the productivity of the mine (Eurasian Scientific Herald, 2024)
In this article, the periodical processes of the mine that should be implemented in the implementation of the mining processes after the design of the mine are mentioned. Open pit mining is a concept focused on improving mine productivity. Taking into account the structure of the mine, the parameters of the mine, we can determine the daily productivity. One of the main problems of open-pit mining is the efficient use of freight traffic and the transport fleet. For maximum efficiency and minimum cost, we need to transport the minerals as close as possible to the mining enterprise's border area after extracting them. Shovels and trucks are widely used loading and hauling equipment in open pit mining around the world. The problem is difficult because truck and shovel systems are complicated by the uncertainties and many parameters associated with truck and shovel operations, and as a result, interactions related to the problem must be considered. This paper develops and implements a stochastic discreteevent simulation model to design and analyze the behavior of a truck and shovel handling system